Diversity analysis of agronomic and nutritional traits of hybrid offspring of forage bermudagrass - Chen, Jianmin; Fan, Shugao; Li, Shuang; Cui, Xinyu; Amombo, Erick; Ji, Mingxia; Liu, Xiaoyan; Fu, Jinmin (Frontiers in Plant Science, 2023)
Because of its excellent stress resistance and forage quality, the forage bermudagrass hybrid population has attracted the attention of scientific researchers in recent years. Studying its genetic diversity can promote the breeding of desirable varieties. The genetic variability in agronomic traits including fresh weight, dry weight, crude ash content, crude protein content, crude fat, Phosphorus content and relative feed value for 56 bermudagrass genotypes were investigated using Wrangler as an experimental reference. Bermudagrass accessions with high forage yield and qualitative attributes were identified using grey relation analysis and cluster analysis. It was found that WCF-34 had the highest total fresh weight (109773.3 kg ha-1) WCF-37 had the highest total dry weight (31951.6 kg ha-1), whereas WCF-26 had the highest crude protein content (16.27%) and WCF-42 had the highest relative feed value (95.32). Combining the results of grey relation analysis and cluster analysis, WCF-42, WCF-34, WCF-38, WCF-37 and WCF-40 were selected from the combined yield traits as high quality bermudagrass. The outcomes of this study will provide a theoretical basis for the breeding and genetic enhancement of bermudagrass.